Non-esterified fatty acid metabolism and postprandial lipaemia. - Frayn, K (1998)
Non-esterified fatty acids (NEFA, or free fatty acids) are an important metabolic fuel. Both the concentration of NEFA and their flux through the circulation vary widely from hour to hour, reflecting nutritional state and physical activity. Inappropriately elevated plasma NEFA concentrations may have a number of adverse effects on both carbohydrate and lipid metabolism. These adverse effects are likely to be most marked in the postprandial period, when NEFA release from adipose tissue is usually suppressed. Although the regulation of NEFA release in the postabsorptive state is well understood in molecular terms, the predominant pathway for release of NEFA in the postprandial state is the action of lipoprotein lipase (LPL) in adipose tissue capillaries on chylomicron-triacylglycerol (TG). Fatty acids released by LPL may either be sequestered in the adipocytes by esterification, or released as NEFA into the plasma. The regulation of this branch-point, which may be of crucial significance for postprandial metabolism, is not well understood. Factors stimulating tissue retention of fatty acids include insulin and acylation stimulating protein. There is considerable indirect evidence that impaired regulation of this step occurs in insulin resistance and other conditions collectively recognised by an elevated concentration of apolipoprotein B (hyper-apo B). Inappropriate release of NEFA in the postprandial period is likely both to reduce the sensitivity of glucose metabolism to insulin and to accentuate postprandial lipaemia. Further study of the regulation of this pathway is much needed.